Apoyo familiar en el proceso de integración escolar de estudiantes con necesidades educativas especiales en educación inicial - Cruz Espinoza, Kenya Suleyca (2021)
Researchers dedicated to school integration highlight the importance of family support as one of the elements that can facilitate or hinder this process. In an exploratory study carried out in the Manuela Saenz Private Educational Unit on a group of parents of Early Childhood Education students with special educational needs, it was possible to verify the existence of certain situations that slowed down the process of their children's school integration. For these reasons, this research was developed whose objective was to strengthen family support in the process of school integration of students with special educational needs and is entitled Family support in the process of school integration of students with special educational needs in Early Childhood Education. A mixed approach was used in the research that was considered descriptive. Methods such as analysis, synthesis, modeling and system approach were used in the study.......